Structural and Functional Analysis of the RNA Transport Element, a Member of an Extensive Family Present in the Mouse Genome - Smulevitch, Sergey (American Society for Microbiology, 2005)
We previously identified an RNA transport element (RTE), present in a subclass of rodent intracisternal A particle retroelements (F. Nappi, R. Schneider, A. Zolotukhin, S. Smulevitch, D. Michalowski, J. Bear, B. Felber, and G. Pavlakis, J. Virol. 75:4558-4569, 2001), that is able to replace Rev-responsive element regulation in human immunodeficiency virus type 1. RTE-directed mRNA export is mediated by a still-unknown cellular factor(s), is independent of the CRM1 nuclear export receptor, and is conserved among vertebrates. Here we show that this RTE folds into an extended RNA secondary structure and thus does not resemble any known RTEs. Computer searches revealed the presence of 105 identical elements and more than 3,000 related elements which share at least 70% sequence identity with the RTE and which are found on all mouse chromosomes. These related elements are predicted to fold into RTE-like structures. Comparison of the sequences and structures revealed that the RTE and related elements can be divided into four groups. Mutagenesis of the RTE revealed that the minimal element contains four internal stem-loops, which are indispensable for function in mammalian cells. In contrast, only part of the element is essential to mediate RNA transport in microinjected Xenopus laevis oocyte nuclei. Importantly, the minimal RTE able to promote RNA transport has key structural features which are preserved in all the RTE-related elements, further supporting their functional importance. Therefore, RTE function depends on a complex secondary structure that is important for the interaction with the cellular export factor(s).